2018
DOI: 10.1063/1.5027579
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive PdCoO2 ultrathin films for transparent electrodes

Abstract: We report on the successful synthesis of highly conductive PdCoO2 ultrathin films on Al2O3 (0001) by pulsed laser deposition. The thin films grow along the c-axis of the layered delafossite structure of PdCoO2, corresponding to the alternating stacking of conductive Pd layers and CoO2 octahedra. The thicknessdependent transport measurement reveals that each Pd layer has a homogeneous sheet conductance as high as 5.5 mS in the samples thicker than the critical thickness of 2.1 nm. Even at the critical thickness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 22 publications
5
50
0
Order By: Relevance
“…1(a)) was confirmed using X-ray diffraction (XRD) ( Fig. S2 [20]), as reported in detail previously [19]. A typical, high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image around the film-substrate interface is shown in Fig.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…1(a)) was confirmed using X-ray diffraction (XRD) ( Fig. S2 [20]), as reported in detail previously [19]. A typical, high-angle annular dark-field scanning transmission electron microscope (HAADF-STEM) image around the film-substrate interface is shown in Fig.…”
supporting
confidence: 78%
“…To overcome this, here we examine ultrathin PdCoO2 films. By altering film thickness [19], we have succeeded in detecting the signal from spin-related transport in these ultrathin films, demonstrating that the surface ferromagnetism occurred within a limited thickness ds near the surface ( Fig. 1(e) and Fig.…”
mentioning
confidence: 93%
“…It was found that this limited the in situ growth temperature to about 300 °C, which was insufficient to drive diffusion, and thus, necessitates an ex situ post-growth anneal to high temperatures to create films with high crystalline quality. These films exhibit improved transport properties compared with the previous PLD grown films [10]. Specifically, the room temperature resistivity of the annealed films approaches that of the best single crystals, suggesting comparable crystalline quality, as confirmed by the STEM data.…”
supporting
confidence: 62%
“…The electrochemical performance of nano CuAlO 2 with an average particle size of ≈20 nm demonstrated 12 times more catalytic activity in the electrolysis of water to the hydrogen evolution reactions and oxygen evolution reactions compared to bulk CuAlO 2 [28]. Research on thin films of delafossite is another interesting and widely investigated area for their potential uses in optoelectronic device fabrication [29][30][31][32]. As has been well established by the high pressure scientific community, compression is yet another way to engineer the crystal/electronic structure of materials, producing compounds with entirely different set of physical properties without altering their chemical composition [33,34].…”
Section: Introductionmentioning
confidence: 99%